MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA GUNUNG SARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Nurhasan, Abdul Khodir; Putri, Febi Rahayu (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
This community service activity discusses the Introduction of Sharia Banks in Gunung Sari Village, Pamijahan District, Bogor Regency. The program to introduce Islamic banks in villages requires a comprehensive approach through education, training and support from the local government, Islamic financial institutions and the local community. The purpose of this community service activity is to provide an introduction to Sharia Banks to the people of Gunung Sari Village, Pamijahan District, Bogor Regency with the hope that the community can better understand the existence of Sharia Banks. The Gunung Sari Village Community Service Method uses the Participatory Transparency method which is prospective in the future through community service activities. The results of this activity were able to provide insight and understanding to the people of Gunung Sari Village, Pamijahan District, Bogor Regency regarding Sharia Banks in detail.